Understanding Usage Behavior of Different Mobile Application Categories Based on Personality Traits - Huseynov, Farid (Oxford Univ Press, 2020)
This study assessed the influence of personality traits on individuals' mobile application usage behavior in different application categories. In the assessment of personality, this study used the well-known Big Five personality traits taxonomy. The Big Five personality traits were measured by using the Mini-International Personality Item Pool scale. Rather than using participants' self-reports about their app usage behavior, this study utilized actual app usage data that were collected via app usage tracker installed in the participants' mobile devices. Instead of focusing on a single category of app, this study assessed the participants' actual behavior across 10 broad and distinct categories of apps. This study showed that personality traits do play an important role in usage behavior of different mobile application categories. Results of this research show that individuals who are extravert and open to experience are more likely to spend time using photography and video editing-related mobile apps. While emotionally stable individuals are less likely to access social networking apps, conscientious individuals tend to stay away from e-commerce-related apps. This research also found that agreeableness is negatively related with access and usage of health and lifestyle mobile apps as well as Internet searching and browsing apps. Application developers and marketers can use the findings of this research to increase users' adoption and usage rate of their apps.
Keywords: the Big Five personality traits; mobile consumer behavior; mobile application categories; mobile app usage behavior; mobile app adoption